Are There Skills Payoffs in Low- and Middle-Income Countries? : Empirical Evidence Using STEP Data - Valerio, Alexandria; Sanchez Puerta, Maria Laura; Tognatta, Namrata; Monroy-Taborda, Sebastian (World Bank, Washington, DC, 2016)
Most research on the economic payoffs of skills has used individuals' level of schooling attained -- typically years or level of education or training received—as a key proxy for skills. Such research has consistently found that individual returns to schooling are positive and that returns tend to be higher in low- and middle-income countries than in higher-income countries. However, years in school is only one proxy for skills -- are these returns still observed using other measures as proxies? This study uses data from the STEP Skills Measurement Survey to examine the extent to which there is an independent association between cognitive and noncognitive skills and earnings in low- and middle-income countries. The study uses measures of reading proficiency and complexity of on-the-job computer tasks to proxy cognitive skills, and personality and behavioral measures to proxy noncognitive skills. The results demonstrate that even when controlling for schooling and background factors, these skills pay off in the labor market. This is particularly the case for the measures of cognitive skills, while noncognitive skills show some significant, but small, effects on earnings. The findings also suggest that there is significant heterogeneity across countries in how skills are valued in the labor market.